2006
DOI: 10.1128/jvi.80.3.1497-1512.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Localization Pattern of Varicella-Zoster Virus ORF29p Is Influenced by Proteasome-Mediated Degradation

Abstract: Varicella-zoster virus (VZV) open reading frame 29 (ORF29) encodes a single-stranded DNA binding protein. During lytic infection, ORF29pis localized primarily to infected-cell nuclei, whereas during latency it appears in the cytoplasm of infected neurons. Following reactivation, ORF29p accumulates in the nucleus. In this report, we analyze the cellular localization patterns of ORF29p during VZV infection and during autonomous expression. Our results demonstrate that ORF29p is excluded from the nucleus in a cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 77 publications
1
35
0
Order By: Relevance
“…The findings in this report coupled with previously published data (59) show that localization of VZV LAPs is regulated in EN by expression of the VZV lytic protein ORF61p. Stallings et al demonstrated that ORF61p expression caused nuclear accumulation of autonomously expressed ORF29p in EN and U373MG cells.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings in this report coupled with previously published data (59) show that localization of VZV LAPs is regulated in EN by expression of the VZV lytic protein ORF61p. Stallings et al demonstrated that ORF61p expression caused nuclear accumulation of autonomously expressed ORF29p in EN and U373MG cells.…”
Section: Discussionsupporting
confidence: 88%
“…Stallings et al previously demonstrated that latent VZV infection of EN can be reactivated after infection with an adenovirus expressing ORF61p. Upon the reactivation of VZV, LAPs such as ORF29p and ORF62p accumulate in the nucleus (59). Accordingly, we tested whether the expression of ORF61p was sufficient to cause the nuclear import of ORF63p in EN.…”
Section: Coexpression Of Orf61p and Orf63p Results In Nuclear Import mentioning
confidence: 99%
See 1 more Smart Citation
“…ORF29 protein is present in the nucleus of lytically infected cells but in the cytoplasm of human neurons during latency (17,25). Interestingly, when an astrocytoma-derived cell line is infected with adenovirus which expresses ORF29, the protein is expressed in the cytoplasm; however, when these cells are treated with a proteosome inhibitor, the half-life of ORF29 protein is increased and the protein migrates to the nucleus (38). Thus, it is possible that overexpression of ORF29 protein in ROka29DR-infected neurons could result in both cytoplasmic and nuclear expression of the protein in the cells and thereby impair latency.…”
Section: Discussionmentioning
confidence: 99%
“…While ORF29 protein is present in the nucleus of lytically infected cells, the protein is in the cytoplasm of neurons from human ganglia (17,25). ORF29 protein localizes to the cytoplasm of guinea pig enteric ganglia neurons (5) and in an astrocyte-like cell line (38). Treatment with a proteosome inhibitor or expression of herpes simplex virus type 1 (HSV-1) ICP0 or VZV ORF61 results in translocation of ORF29 protein to the nucleus in both guinea pig enteric ganglia neurons and the astrocyte-like cell line.…”
mentioning
confidence: 99%